Optic Disc Features in Highly Myopic Eyes: The ZOC-BHVI High Myopia Cohort Study. Issue 4 (April 2018) - Li, Zhixi; Guo, Xinxing; Xiao, Ou; Lee, Pei Ying; Liu, Ran; Wang, Decai; Sankaridurg, Padmaja; He, Mingguang
Abstract : SIGNIFICANCE: Some studies reported that optic disc tilt and rotation might be risk factors for the susceptibility of high myopic eyes to develop glaucoma. However, data regarding optic disc manifestations in high myopia participants are few. It is crucial to characterize the features of optic disc manifestations among high myopes. PURPOSE: To describe optic disc characteristics of Chinese highly myopic eyes and to investigate associated factors. METHODS: This cross-sectional, observational study included 890 Chinese with bilateral high myopia (defined as ⩽−6.00 diopters spherical power) in 2012. All subjects underwent cycloplegic autorefraction, ocular biometry, and fundus photography. The optic disc tilt ratio, degree of rotation, and β-zone peripapillary atrophy area were measured from the 45°optic disc-centered fundus photographs. Optic disc tilt was defined as optic disc tilt ratio, the ratio of maximum to minimum diameter of optic disc, exceeding 1.3. The definition of optic disc rotation was using optic disc rotation degree, the angle from long diameter and the vertical meridian, of >15°. RESULTS: Among 890 participants, 2 were excluded by ungradable optic disc-centered fundus photographs. In the 888 studied right eyes, the mean spherical power was −9.36 ± 3.46 diopters with a mean axial length of 27.51 ± 1.63 mm. The proportion of optic disc tilting, rotation, and β-zone peripapillary atrophy were 81.2%, 48.3%, and 92.8%, respectively. The mean ratio of optic disc tilting and rotation degree was 1.78 ± 0.53 and 21.08 ± 19.91°; the mean area of β-zone peripapillary atrophy/optic disc head was 1.11 ± 1.22. A multiple linear regression showed that older age ( P < .001), female ( P = .02), and more myopic spherical equivalent ( P = .005) were related to the greater optic disc tilting ratio. CONCLUSIONS: Beta-zone peripapillary atrophy, optic disc tilting, and rotation are very common in highly myopic eyes in Chinese population. Older age, female, and more myopic spherical equivalent are risk factors of higher degree of optic disc tilting.